The Efficiency of Drone Propellers—A Relevant Step Towards Sustainability - Jaan Susi; Karl-Eerik Unt; Siim Heering (Engineering Proceedings)
The static efficiency of a propeller cannot be determined in the same way as for propellers operating in the presence of freestream airflow. As various kinds of multirotor drones and small UAVs operate in hovering or nearly hovering modes, it is necessary to develop methods for determining and measuring the static aerodynamic efficiency of small-scale propellers. Propellers with a Reynolds number near the 0.75 R, where the blade section is less than 500,000, are considered to be at a critical value, i.e., the estimated border between two flow modes—laminar and turbulent. The efficiency of small-scale propellers may be hard to predict through modeling, making direct empirical measurements invaluable in this situation.